Neo-normative control: An impetus for Millennials or a hoax? - Khan, Salar (2017)
Being born in a world that experienced technological advancements along with 24/7 interconnectedness via the internet and social media, the Millennials grew up to be individuals that consist of work values that are antithetical to those of their older generational cohorts such as, Traditionalists and Baby boomers. These generations of the modern era exhibited emphasis on modernist, survival values such as power, prestige, and material benefits due to war struck nations where financially securing families became the foremost priority for all concerned individuals. On the other side of the discourse, Millennials of the postmodern era that experienced times of economic prosperity, display work values that are inclined towards not only personal development and passions, but also the need to bring positive impact to the society by entrepreneurial ambition and solutions. As this change in mindset continues to exist, it has cornered organisations in a position where they too must undergo change in order to understand, retain, and motivate their employees. From bureaucratic control of modern organisations to neo-normative control of the postmodern era, this research seeks to compare these in contrast and justify why both forms of control are adequate tools for their respective generations. As we involve Kafka’s critique of bureaucracy in the midst of this discourse, we finally see a path that combines both nuances and brings forth a perspective that sheds light upon the future of generations and organisations.